Pendekatan Kecerdasan Emosional Dalam Pembelajaran Daring Bahasa Arab - Amir Reza Kusuma; Didin Ahmad Manca (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study examines the emotional intelligence approach that is applied to learning Arabic in Indonesia. This research uses descriptive research, namely research based on literature review which is described through descriptions using library sources such as books, journals and laws, and regulations related to the research topic. In this study, it is explained that the use of an emotional intelligence approach in learning Arabic has great benefits on the learning development of students. There are many obstacles faced by teachers and students in the learning process, such as the difficulty of understanding the material to increase student stress levels. Therefore, an emotional intelligence approach is needed in this learning process so that students can motivate themselves, be able to control themselves to be responsible for their duties as students